A new species of Masaris Fabricius from Iran (Hymenoptera: Vespidae: Masarinae) - Selis, Marco (Zootaxa, 2019)
A new species of Masaris Fabricius, 1793 from Iran, Masaris agnolii Selis, sp. nov., is described and figured based on a single male.